2004
DOI: 10.1002/app.21031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mechanical properties of sisal–polyester composites as a function of the polyester matrix formulation

Abstract: ABSTRACT:In this work a comparative study on the impact and tensile properties of polyester/sisal fiber reinforced composites was undertaken. The polyester matrix was used bare and modified with: (1) a silane coupling agent; (2) a flame retardant system; and (3) a blend of the silane agent and the flame retardant system. The experimental results show that the flame retardant acts as a particulate reinforcement to the polyester matrix and the silane coupling agent acts as a plasticizer. The simultaneous additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Além destas aplicações, a literatura relata diversos estudos sobre a modificação da superfície das fibras com objetivo de sua utilização em materiais compósitos poliméricos de grande interesse para a indústria [1,3,7,8,10,[12][13][14][15][16][17][18][19][20] . Os compósitos reforçados com fibras de sisal se destacam por apresentarem alta resistência ao impacto, e boas propriedades de resistência à tração e flexão [3,[21][22][23][24] .…”
Section: Methodsunclassified
“…Além destas aplicações, a literatura relata diversos estudos sobre a modificação da superfície das fibras com objetivo de sua utilização em materiais compósitos poliméricos de grande interesse para a indústria [1,3,7,8,10,[12][13][14][15][16][17][18][19][20] . Os compósitos reforçados com fibras de sisal se destacam por apresentarem alta resistência ao impacto, e boas propriedades de resistência à tração e flexão [3,[21][22][23][24] .…”
Section: Methodsunclassified
“…The high energy to break off surface-treated composites indicates that the matrix is controlling the growth of cracks as fracture proceeds. Work carried out by Fonseca et al, (2004) showed that sisal polyester composites resulted a tensile strength, tensile modulous, impact strength of 7 MPa, 1.7GPa and 328±65 respectively. However, the elongation at break (1.7%) found to be higher than that of the similar polyester sisal composites as reported by Singh et al, (1996).…”
Section: Sisal Polyester Compositementioning
confidence: 99%
“…A weak fibre-matrix interface was expected for this composite, since no fibre treatment or matrix modification was performed. The weak interface and the low fibre volume fraction employed are held responsible for the low mechanical properties and premature failure of that composite (Fonseca et al, 2004). …”
Section: Sisal Polyester Compositementioning
confidence: 99%
“…When PEG was used as an alcohol comonomer, the copolyester FDY showed a lower reduction ratio compared with the homo polyester FDY, which was due to the structural characteristics of the PEG introduced in the copolymerization. On the other hand, the reduction ratio of the copolyester FDY prepared from TMP, TMA, or IPA was higher than that of the homo polyester FDY [15].…”
Section: Resultsmentioning
confidence: 99%